On the Durability of Sealable Circular Concrete Structures under Chloride Environment - Changwen Mi; Kaikai Shao; Xiaobao Li (Advances in Materials Science and Engineering)
Reinforcement corrosion resulting from chloride attack is one major mechanism that compromises concrete durability. Numerical methods were commonly used for tackling Fick’s diffusion equations. In this paper, we developed a Crank-Nicolson based finite difference scheme suitable for circular concrete structures. Both a time-dependent surface chloride model and diffusivity were considered. The impact of an ideal sealer on chloride redistribution was further investigated. Results suggested that the chloride threshold depth in a concrete structure is greatly affected by the radius of curvature, environment severity, and diffusivity. For sealable concrete structures, both the sealer application timing and location are of great importance.